Implementasi Kurikulum dan Metode Pembelajaran Pendidikan Agama Islam di Sekolah Darul Muhmin, Khuan Kalong, Satun - Hartono, Muhammad Purqon Azmi; Ruslan, Muhammad (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Islamic Religious Education (IRE) plays a crucial role in shaping students’ character amidst globalization. At Darul Muhmin School in Khuan Kalong, Satun, Thailand, IRE is implemented through a structured curriculum and Islamic-based pedagogical methods. However, challenges such as limited parental involvement, poor infrastructure, and an unsupportive external environment hinder its effectiveness. Using a qualitative case study approach, this research explores the implementation of the IRE curriculum and teaching strategies. Findings indicate that the school has maximized existing resources, strengthened community participation, and provided teacher training to overcome barriers. These initiatives have led to increased parental support, better learning facilities, and greater student engagement in religious practices. The study concludes that despite external constraints, the school has effectively fostered a learning environment conducive to Islamic character development. These insights offer valuable implications for other institutions aiming to enhance the delivery of Islamic Religious Education.